2017
DOI: 10.3390/agronomy7010024
|View full text |Cite
|
Sign up to set email alerts
|

A Survey: Potential Impact of Genetically Modified Maize Tolerant to Drought or Resistant to Stem Borers in Uganda

Abstract: Abstract:Maize production in Uganda is constrained by various factors, but especially drought and stem borers contribute to significant yield losses. Genetically modified (GM) maize with increased drought tolerance and/or Bt insect resistance (producing the Bacillus thuringiensis Cry protein) is considered as an option. For an ex ante impact analysis of these technologies, a farmer survey was carried out in nine districts of Uganda, representing the major farming systems. The results showed that farmers did ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Several studies (Mwalusepo et al 2015, Goftishu et al 2017, Keno et al 2018, and Abate 2012 have looked at the impact of stemborer on yields and the factors that predispose crops to infestation. We define the probability of infestation and damage following Wamatsembe et al (2017) who, based on farmers evaluations, estimated the average frequency of significant stemborer damage at two years out of three, an average risk of 67 percent across all years. We applied this same risk value to all regions.…”
Section: Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Mwalusepo et al 2015, Goftishu et al 2017, Keno et al 2018, and Abate 2012 have looked at the impact of stemborer on yields and the factors that predispose crops to infestation. We define the probability of infestation and damage following Wamatsembe et al (2017) who, based on farmers evaluations, estimated the average frequency of significant stemborer damage at two years out of three, an average risk of 67 percent across all years. We applied this same risk value to all regions.…”
Section: Probabilitiesmentioning
confidence: 99%
“…As in the case of Ethiopia, stemborer damage and drought stress cause substantial losses in Uganda's maize production. According to Wamatsembe et al (2017), average yield losses due to drought alone in SSA are estimated at about 33 percent as the result of dependence on rainfed conditions in regions with insufficient and or uneven spread rains during crop growth. Losses due to drought were about five percentage points higher for low input farmers than high input farmers (60 and 54 percent, respectively).…”
Section: Probabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize production can be increased by up to 2 to 5 million tons under moderate drought which can feed about 14 to 21 million people (Cenacchi and Koo, 2011). Wamatsembe et al (2017) indicated in a survey study that drought and stem borer damage were on average 54.7% and 23.5%, respectively, with corresponding estimated yield losses of 36.5% and 15.6% in Uganda. If and when Bt maize and DT maize are grown in Uganda, the ex-ante partial budget analyses for profitability of the two individual traits reveal an average value/cost ratio of 2.1 for hybrid Bt maize and 1.5 for drought tolerant maize (Wamatsembe et al, 2017).…”
Section: Ir (Bt) Eggplant Was Developed By Maharashtramentioning
confidence: 99%
“…Wamatsembe et al (2017) indicated in a survey study that drought and stem borer damage were on average 54.7% and 23.5%, respectively, with corresponding estimated yield losses of 36.5% and 15.6% in Uganda. If and when Bt maize and DT maize are grown in Uganda, the ex-ante partial budget analyses for profitability of the two individual traits reveal an average value/cost ratio of 2.1 for hybrid Bt maize and 1.5 for drought tolerant maize (Wamatsembe et al, 2017). It is imperative that combining the two traits together in one hybrid such as DT/Bt could increase this average value/cost ratio.…”
Section: Ir (Bt) Eggplant Was Developed By Maharashtramentioning
confidence: 99%